PENGARUH SANKSI, ADMINISTRASI, KUALITAS OELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BUMI DAN BANGUNAN DI KECAMATAN RAO KABUPATEN PASAMAN - Afrianti1, Dina; Ramayan, Citra; Areva, Desi (Pendidikan Ekonomi, 2014)
ABSTRACTÂ This study aims to test 1 ) The effect of sanctions on tax compliance in paying property taxes , 2 ) Effect of administration on tax compliance in paying taxes on land and building 3 ) Effect of quality of service tax on tax compliance in paying taxes on land and buildings 4 ) the effect of sanctions , administration , quality of service on tax compliance in paying taxes earth and building .This type of research is causative . The population in this study are all taxpayers in the sub-district Rao regency Pasaman . This study uses a sampling technique is accidental sampling, by using the formula Slovin . The data analysis technique used is multiple regression with the help SPSS. The results showed that : 1 ) Sanctions significant positive effect on tax compliance with tcount > ttable ie 6.641 > 1.660 ( significance 0.000 < Î± 0.05 ) which means that Î²1 is accepted . 2 ) Administration of a significant positive effect on tax compliance with tcount > ttable ie 3.443 > 1.660 ( significance 0.003 < Î± 0.05 ) which means that Î²2 is accepted . 3 ) Quality of service tax a significant positive effect on tax compliance with tcount > ttable ie 4.872 > 1.660 ( significance 0.000 < Î± 0.05 ) which means Î²3 is accepted . 4 ) Sanctions , Administration , Quality Tax Services together have a significant effect on tax compliance . Suggestions in this study were : 1 ) To be able to increase the tax authority to enforce penalties or taxes to taxpayers who are less adherent . 2 ) In order to further improve the tax agency administrative section , so that the taxpayers get the ease of tax administration process . 3 ) In order for the tax authorities to further improve the quality of service that taxpayers feel more comfortable and more obedient in the process of tax payment .